High-resolution X-ray emission study for Xe54+ on Xe collisions - Herdrich, Marc Oliver; Hengstler, Daniel; Keller, Michael; Geist, Jeschua; Schötz, Christian Dominik; Krantz, Matthäus; Fleischmann, Andreas; Enss, Christian; Gaßner, Tobias; Hillenbrand, Pierre-Michel; Gumberidze, Alexandre; Spillmann, Uwe; et al. (The European physical journal. D, Atomic, molecular, optical and plasma physics, 2023)
We report on an experiment conducted at the ESR storage ring aiming at the study of the X-ray emission of $$\text {Xe}^{54+}$$ions colliding with Xe atoms at a beam energy of 50 MeV/u. The radiation resulting from the ion-atom interaction was observed using a high-resolution spectrometer based on metallic-magnetic calorimeter technology. In order to benchmark the capabilities of these detectors for high-precision atomic physics experiments, we identified several transitions from H-like and He-like xenon and determined their energies. Furthermore, the 1s-Lamb shift in $$\text {Xe}^{53+}$$was estimated using the measured line energies. The results are compared with previous experimental studies and theoretical predictions.
Im Titel ist bei Xe54+ die Zahl 54+ hochgestellt
Gesehen am 30.08.2023